A facile and scalable Fe-Cr decorating strategy to boost the lithium storage of SiOx anode. (20th February 2022) - Zhou, Xiaozhong; Qi, Zhaoyi; Jiang, Yuyuan; Yan, Pengfei; Ding, Juanxia; Wang, Haiyan; Lu, Hongkai; Liu, Dongxu; Dong, Kaifa; Tang, Yougen; Sun, Dongfei; Lei, Ziqiang
Highlights: Fe-Cr alloy is employed as an efficient booster for lithium storage in sio x -based electrode. Electrochemical de-alloying process of low-valent Li x Si (0 ≤  x  ≤ 2) is boosted during cycling. The ICE, cycling stability and rate capability of electrode are greatly improved. Abstract: SiO x is regarded as a promising anode material for the next-generation lithium-ion batteries with high energy density. However, the reduplicative volume changes during cycling cause the pulverizations of Si, leading to decreased utilization of active Si component and poor cycling performance. Herein, a facile and scalable Fe-Cr decorating strategy is reported to boost the lithium storage of SiO x anode. Our comprehensive characterizations indicate that there are strong interactions between Fe-Cr and SiO x during a facile ball milling process. After cycling, Fe-Cr nanoparticles are dispersed in the in-situ formed lithium silicates and Li2 O matrix, which can maintain superior conductivity of lithium ion and electron for the active components through point-to-point connections. This unique structure boosts the electrochemical de-alloying process of the low-valent Li x Si (0 ≤  x  ≤ 2), and increases effective utilization of the active Si component during cycling, resulting in improvement of reversible capacity and cycling stability. This bm SiO x -FeCr electrode can deliver high reversible specific capacity (1370 m Ah g −1 at 200 mA g −1 ), good rate capability (653.8 m Ah g −1 at 2000 mA g −1 ), and superior cycling stability. This work provides a promising route for improving the utilization of active Si component and the structural stability of SiO x -based anodes. Graphical abstract: Image, graphical abstract